Variabilidade Espacial do Desenvolvimento e da Produtividade do Trigo Triticum aestivum - Roman, Mari (2005)
This work had by objective to study and to model the spatial variability of variables relative at the wheat development cultivated in year 2003 in 22,62 ha pertain at Central Co-operative of Agricultural Research (COODETEC). Went used the cultivates Coodetec 101 (3,52 ha) and Coodetec 103 (18,10 ha). The samples went colected in gride of 50 x 50 m, totalized 89 points, the analysis unity a square with 0,25 m2. Went obtained data of emergency seedling, number of s-shoot, height of plants, number of spikes, length spikes, number of grain by spike, weight of thousand seed and production. The spatial dependence went more clear by mean number of s-shoot collected 60 days after to sow and crop height of plants. Variables with relation at the spike and the number of s-shoot 30 days after sow don t had spatial dependence. The others variables went considered with spatial dependence. To the variable spatial independence, compared the mean between the cultivates, and by mean number of s-shoot collected 30 days after to sow and length spikes the mean had difference signification in level of 5 %, by Tukey test. Went made prediction of all variables, spatial dependence or independence, to places no sampled by kriging technical and begot contour maps. There was spatial correlation negative and positive between variables, with correlation range of 200 till 700 m.